Cytostatic hydroxycoumarin OT52 induces ER/Golgi stress and STAT3 inhibition triggering non-canonical cell death and synergy with BH3 mimetics in lung cancer. (1st March 2018) - Lee, Jin-Young; Talhi, Oualid; Jang, Dongman; Cerella, Claudia; Gaigneaux, Anthoula; Kim, Kyu-Won; Lee, Jung Weon; Dicato, Mario; Bachari, Khaldoun; Han, Byung Woo; Silva, Artur M.S.; Orlikova, Barbora; et al.
Abstract: Coumarins are natural compounds with antioxidant, anti-inflammatory and anti-cancer potential known to modulate inflammatory pathways. Here, non-toxic biscoumarin OT52 strongly inhibited proliferation of non-small cell lung cancer cells with KRAS mutations, inhibited stem-like characteristics by reducing aldehyde dehydrogenase expression and abrogated spheroid formation capacity. This cytostatic effect was characterized by cell cycle arrest and onset of senescence concomitant with endoplasmic reticulum and Golgi stress, leading to metabolic alterations. Mechanistically, this cellular response was associated with the novel capacity of biscoumarin OT52 to inhibit STAT3 transactivation and expression of its target genes linked to proliferation. These results were validated by computational docking of OT52 to the STAT3 DNA-binding domain. Combination treatments of OT52 with subtoxic concentrations of Bcl-xL and Mcl-1-targeting BH3 protein inhibitors triggered synergistic immunogenic cell death validated in colony formation assays as well as in vivo by zebrafish xenografts.